Coda: materials-in-interaction as assemblages, grammars of action, and phenomenological activity. Issue 1 (3rd April 2021) - Guerrettaz, Anne Marie
ABSTRACT: This coda begins by briefly discussing the constructs at the heart of this special issue – materials use, classroom discourse, materiality, and materials – highlighting how the compilation contributes to the expanding definition of language learning and teaching materials. I then discuss two interrelated guiding questions of this compilation – how materials and discourse influence one another – and posit that an important first step for the field is conceptualising the nature of materials-in-interaction (i.e., the materials-discourse interface). The majority of the article then goes on to explore three ways of (re)conceptualising and studying materials use with a focus on the materials-interaction interface, examples of which are identifiable across the empirical articles of the issue. These include reconceptualizations of 'materials use' as: 1) assemblages, 2), 'grammars of action' and 3) 'phenomenological activity'. The first two are somewhat novel concepts in language education research. The third, 'activity', is a 'common sense' construct in the field which has surprising not been well defined from an empirical, 'phenomenological', and 'theoretically neutral' perspective. The article concludes with a brief discussion about aspects of 'materials use' that are evident in all three conceptualisations of materials-in-interaction.